PENGARUH PROGRAM UPAYA KHUSUS (UPSUS) TERHADAP PRODUKTIVITAS, BIAYA POKOK PRODUKSI DAN PENDAPATAN USAHATANI PADI DI KABUPATEN PRINGSEWU - Desti April Yanti; Agus Hudoyo; Achdiansyah Sulaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
Rice is the staple food of Indonesian people. In 2014, its production was less than its need including its losses. Therefore, during 2015-2020, in order to increase the production through increasing its yield and its cropping intensity, the Ministry of Agriculture had been implementing the program of Upaya Khusus, called Upsus. The Upsus could be success if the farmers who participated in this program spent less the rice standard cost and obtained bigger profit. The question was whether the Upsus could increase yield, decrease standard cost and increase profit. Accordingly, the objective of this study was to answer this question. There were 30 respondents chosen by the simple random sampling method from six villages of three subdistricts. Each respondent was interviewed his farming budget in four seasons, i.e. rainy season 2014/2015, dry season 2015, rainy season 2017/2018, and dry season 2018. Consequently, the number of observation was 120. The data farming budget were used for getting the three following variables, i.e. yield (ton/ha), production standard cost (Rp/kg), and profit (Rp million/ha). The data were analyzed by using three multiple regression models. This study revealed that the Upsus was statistically significant on increasing its yield, decreasing its standard cost and increasing its profit. By implementing the Upsus, the increment in yield and profit of rice farming were 3 percent and 30 percent, respectively. The decrease in standard cost was 6 percent. The average yield, the standard cost and the profit of rice farming in Upsus were as follows 5,20 ton/ha, Rp4.154,-/kg and Rp6,82 million/haKeywords: profit, standard cost, upsus, yield